Thermal characterization of shape-stable phase change material for efficient thermal energy storage and electric to thermal energy conversion - Yadav, Aman; Mahendran, Samykano; Pandey, A. K.; Rajamony, Reji Kumar; Tyagi, V. V. (Elsevier Ltd, 2024)
PCMs low thermal conductivity and leakage problem hindered their widespread use in TES applications. In the present research, a newly synthesized porous structured 3-D expanded graphite (EG) additive is used to improve low thermal conductivity and provide shape stability to a PCM. Herein, EG particles were synthesized using expandable graphite with the help of a tube furnace at 900 ◦C for 35 min. Further, shape-stable phase change materials (SS-PCMs) were developed by infusing EG particles into liquid A70 (PCM) using the vacuum impregnation method. The experimental results revealed that EG particles improved the low thermal conductivity and reduced the leakage problem of PCMs. The newly developed SS-PCMs demonstrate an outstanding thermal conductivity of 1.59 W/(m⋅K), increased by 657.16 % compared to base (A70) PCM. Additionally, 500 thermal cycles were carried out on the SS-PCM composites. The composite showed a minimum change in the thermophysical properties based on the results. Moreover, an electro-thermal energy conversion experiment was conducted to analyze the developed SS-PCM thermal energy efficiency, and the SS-PCM composite achieves a transformation capability of 70.89 % when operated at 4.8 V. In conclusion, superior thermal conductivity is shown by newly developed SS-PCMs with 3D expanded graphite, which are perfect for ensuring efficient thermal management in electronic devices and energy storage systems.